Comparative Study on the Performances of PV System with Various Combinations of Converter Topologies and PWM Types - Syahierah Eliya, Sabri; Muhamad Zahim, Sujod; Mohd Shawal, Jadin (Universiti Teknikal Malaysia Melaka (UTeM), 2018)
Increasing demand for electricity generated from renewable energy sources forced power utility provider to develop more and larger power plant. In Malaysia, among renewable energy sources, photovoltaic (PV) is the most reliable. Hence, large-scale PV power plants have been developed and many more to be developed in the future. In case of large GridConnected PV (GCPV) power plant, the converter which is nonlinear load will generate Total Harmonic Distortion (THD) into the electrical power system. Harmonic generated by the PV system may downgrade the quality of power grid and affect the reliability and safety. In addition, other main concerns in GCPV system are switching losses of the switching devices in the converter and the cost of the converter. These performances can be improved by the right choice of Pulse Width Modulation (PWM) type and converter topology. This paper will discuss which PWM type and converter topology should be chosen to produce the optimal performance based on THD, switching losses and cost. In general, the best combination is a two-level converter with continuous PWM (CPWM) where the cost is almost half compared to the three-level converter and having optimal value in the combined performance of THD and switching losses.